Effects of polarity of rubber structure on electrical impedance and conductivity / Shahin Shahadah Ali Nafiah - Ali Nafiah, Shahin Shahadah (2008)
Electrical conductivity of rubbers blends with variation of blend ratio and virgin rubbers that have different polarity such as NR (SMR 10), NBR (ACN 33%, ACN 55%) and ENR (ENR25, ENR-50) were investigated through Impedance Spectroscopy HIOKI 3532-50 LCR HiTESTER Version 4.03E. Two-roll mill machine was used to masticate the rubber and sheet to a thickness of about 1mm. Virgin NR (SMR 10) was blended with NBR (ACN 33%) by using two-roll mill with different ratio. Each blend ratio will result in different polarity and electrical conductivity. The electric conductivity will increase as the polarity of the rubber is increased. The polarity of the rubber can be describe by refer to their molecular structure. NBR rubber with 55% of ACN content has the high polar thus it has the highest electrical conductivity among the other rubber. High composition of ACN content in NBR may increase the polarity of NBR rubber. Polar functional groups of nitrile group that attach to the ACN cause the rubber become polar. Natural rubber (SMR 10) has the lowest electrical conductivity because SMR 10 has no polar molecule. Polar molecule may influence the transportation or movement of electrons (charges) in the rubber particles, thus electrical conductivity can be generated easily and cause high electrical conductivity.